A própria vida: efeitos de real e de sinceridade nas autoficções de Julián Fuks e de Karl Ove Knausgård - Silva, Camilo Gomide Cavalcanti (2017)
This work aims to analyze the effects of reality and sincerity in the autofictions A resistência, by Brazilian writer Julián Fuks, and Minha luta, by Norwegian writer Karl Ove Knausgård. These contemporary authors seek a new form of realistic expression in their works. Both start from a lack of interest in traditional fiction, with fictional plots and characters, and choose to write about their own life, finding greater legitimacy in the autobiographical. Autofiction was coined in the 1970s to define a practice which became popular among writers interested in telling their own story. Although it is inevitably contaminated by fiction, many authors have found in this genre a means of seeking new effects of reality and authenticity. This research intends to understand how these writers forge these impressions from something so notoriously fallible as memory. The theoretical foundations of this research have, as a starting point, the seminal analyses of Michel Foucault on the writings of the self and the study of Jean Starobinski on the Confessions of Rousseau. From the literary field, Roland Barthes’ studies on realism and the limits of representation are considered, as well as other theorists dedicated to the themes of autobiography and autofiction, such as Lejeune (2014), Doubrovsky (1977) (who coined the term autofiction) and contemporary researchers such as Schøllhammer (2009), Klinger (2012), Faedrich (2016) and Perrone-Moisés (2016). The conclusion of this research is that both Fuks and Knausgård find, in autofiction, a form of greater commitment to literature. The difference, however, is that in A resistência, the effect of reality comes from the narrator’s constant suspicion of his own narrative; and in Minha luta, this effect comes from the corrosive confession of the narrator, who deeply identifies with the author